ZnO nanostructures: a heterogeneous catalyst for the synthesis of benzoxanthene and pyranopyrazole scaffolds via a multi-component reaction strategy. Issue 7 (16th September 2020) - Chhattise, Prakash; Saleh, Suheb; Pandit, Vikram; Arbuj, Sudhir; Chabukswar, Vasant
Abstract : A hydrothermal technique is employed for the preparation of nanostructured ZnO. Abstract : A hydrothermal technique is employed for the preparation of nanostructured ZnO. The reaction was carried out at 180 °C for 2 h in the presence of ethylenediamine (EDA) as a capping agent and was characterized by X-ray diffraction (XRD), scanning electron microscopy (FESEM), and transmission electron microscopy (TEM). XRD indicates the formation of highly crystalline ZnO having a wurtzite structure. FESEM analysis validates the formation of a submicron size spherical shaped marigold flower like morphology. The nanostructured ZnO was screened for its catalytic activity as a heterogeneous catalyst for the multicomponent synthesis of benzoxanthenes and pyranopyrazole derivatives in good to excellent yield. The major advantages associated with this methodology include ease of separation and reusability of the catalyst, easy work-up and short reaction time.